Women’s Representation in Climate Change Efforts in Indonesia - Fitriana, Wulan; Mubdi, Umar (Közigazgatási és Infokommunikációs Jogi PhD Tanulmányok, 2026)
Climate change is an intertwined issue with implications on the enjoyment of human rights and social justice. Female members in Indonesia are more vulnerable due to their linkage with certain industries and sectors which are exposed to climate change. This article explores the issues of legal politics associated with representation of women in climate change policies in Indonesia, as well as provides suggestions regarding the policy framework to secure representation of women in a transformative way. This research is conducted on a doctrinal approach to the problem based on legislation and conceptual frameworks, as well as best practices of other developing countries. According to the results of the analysis of literature sources, there are no doubts about the strong commitment of Indonesia to its constitution and other international instruments. However, at the same time, there is evidence that the process of formulating climate change policy in Indonesia is gender-neutral and sectoral. Thus, a gender transformative adaptation policy paradigm becomes crucial for the success of climate change and sustainability policy.